'Palaeolago Fueguino', a Late Pleistocene lacustrine basin located in the central sector of Tierra del Fuego: a seismostratigraphic study. (9th February 2021) - Lozano, Jorge G.; Bran, Donaldo M.; Donda, Federica; Lodolo, Emanuele; Esteban, Federico D.; Tassone, Alejandro
Abstract: At 20 ka bp, lakes Yehuin, Chepelmut and Fagnano constituted a single, large water body in the central part of Isla Grande de Tierra del Fuego (southernmost Patagonia). The evolutionary history of this lake, known as 'Palaeolago Fueguino', was probably controlled by the advances, stillstands and retreats of the 'Fagnano Palaeoglacier', an outlet glacier that flowed eastward from the Darwin Cordillera ice sheet. A detailed analysis of high‐resolution seismic reflection profiles acquired within the three lakes has allowed the identification and correlation of seven unconformities within the lacustrine sedimentary infill, three seismostratigraphic sequences in Lago Fagnano and four in Lago Yehuin. A seismic stratigraphic correlation between these sequences suggests that these basins formerly constituted a single, large lacustrine body. A lake‐level curve of the evolutionary stages of each lake, derived from the seismostratigraphic analysis of the sedimentary infill is proposed here, representing a 17.5 ka‐long record. It was further integrated with the glacial record of the advances and retreats of the Fagnano Palaeoglacier. This study has implications for interpreting the sedimentary history of lake basins in glaciated mountain ranges.